INVESTIGATING MOTIVATION OF PRIMARY AND SECONDARY SCHOOL TEACHERS IN TERMS OF DEMOGRAFIC VARIABLES ACCORDING TO TEACHER OPINIONS: A CASE OF TURKEY - Recepoğlu, Ergün (Scientia Socialis Ltd, 2013)
Motivation is of great importance for social and work life as motivation emerges in every aspect of life. The aim of this research is to analyze job motivation of primary and secondary school teachers. This is a descriptive research in the survey model. The sample of the study is 305 teachers employed in primary and secondary schools in Karabük in Turkey. As a data collection instrument “Job Motivation Scale” developed by Aksoy (2006) was used. The frequency, percentage, arithmetical mean and standard deviation of the answers were calculated. Independent t-Test and One-Way ANOVA were performed to analyze the data. According to research findings, Job motivation of teachers in primary and secondary schools shows a significant difference in terms of age, tenure of office while motivation of teachers do not show a significant difference in terms of teachers’ gender, education level and branch. Key words: motivation, primary and secondary school, teacher.
Keywords: 4. Education